Allelopathic effects of rubber tree (Hevea brasiliensis (Willd. Ex A.Juss.) Müll.Arg.) on germination and initial growth of lettuce (Lactuca sativa L.) (Research, Society and Development, 2021)
The knowledge on allelopathy can assist in the cultivation system and the effects on positive and negative interactions among plants. Therefore, the knowledge on this topic is of great importance to assist on ecological and management strategies of the Rubber-tree (Hevea brasiliensis (Willd. ex A.Juss.) Müll.Arg.), species of economic prominence in the latex sector worldwide. The objective of this study was to test the allelopathic effect of the rubber tree (H. brasiliensis) on the germination of the bioindicator species Lettuce (Lactuca sativa L.) in order to detect possible allelopathic effects. For this study, an aqueous extract obtained from the mature leaves of H. brasiliensis was used in the concentration of 200g/L. A treatment with the aqueous extract and a control treatment without the extract with 10 repetitions of 10 seeds per treatment were used. A germination assay was employed to test the germination percentage (G%), root length and potential root respiration activity of seedlings using tetrazolium. The data obtained were submitted to the Mann-Whitney test (p